Pitfalls of computed tomography angiography examination in veno-arterial extracorporeal membrane oxygenation patients: a case report of a patient with cardiac rupture - Hua-Liang Ying; Hui Zhao; Chao Zhang; Mengyuan Zhang; Weijun Song; Yongpo Jiang (Journal of Cardiothoracic Surgery)
Abstract Background Veno-arterial (V-A) extracorporeal membrane oxygenation (ECMO) is commonly used for patients with cardiac arrest, cardiogenic shock, or heart failure and is a life-saving technique. Computed tomography angiography (CTA) examination in patients on ECMO presents certain challenges. Due to the dual circulation characteristics of blood flow in ECMO patients, vascular imaging and interpretation can be difficult and may even present pitfalls. Case presentation A 59-year-old male was admitted with a diagnosis of cardiogenic shock due to “sudden onset of chest discomfort for 6 hours and altered mental status for 4 hours”. He underwent V-A ECMO treatment twice and had two aortic CTA examinations. The initial CTA mistakenly diagnosed an aortic dissection. Considering the dual circulation blood flow characteristic in ECMO patients, a second CTA was performed. Combined with echocardiography, the patient was accurately diagnosed with left ventricular rupture and underwent left ventricular rupture repair surgery. The patient was successfully weaned off ECMO, transferred out of the ICU, and eventually discharged in good condition. Conclusion The unique hemodynamics of V-A ECMO patients necessitate interpreting CTA examinations with an understanding of the dual circulation characteristic to avoid misdiagnosis.